Analyzing Spending Behavior Among Generation Z Students in Surabaya: The Mediating Role of Digital Financial Literacy - Jannah, Ulfa Rizkiatul; Yuniningsih, Yuniningsih; Nur, Dhani Ichsanuddin (Majalah Ilmiah Bijak, 2025)
This study uses a quantitative method with an explanatory research approach that aims to test the mediation of digital financial literacy on the influence of herding, money attitude, and financial experience on spending behavior in generation Z students in Surabaya. The research material is based on the problem of spending behavior which is increasing every year while the percentage of growth is unstable or tends to decline. Data were collected through a survey with a questionnaire as a research instrument. The study population included all generation Z students in Surabaya City, with a sample of 400 students selected using saturated sampling techniques. Data analysis was carried out using SmartPLS.From this study, the results show that herding behavior, money attitude, and financial experience contribute to spending behavior. Herding behavior and money attitude contribute to spending behavior through digital financial literacy. While digital financial literacy does not provide a significant contribution to financial experience on spending behavior.